Toward product-based regulation of crops: Current process-based approaches to regulation are no longer fit for purpose - Gould, Fred; Amasino, Richard, M.; Brossard, Dominique; Falck-Zepeda, José B.; Dixon, Richard A.; Gallo, Michael A. (American Association for the Advancement of Science, 2022)
Current process-based approaches to regulation are no longer fit for purpose